Plastic deformation of polymer matrix composites reinforced with beaded fibers. (1st December 2022) - Xu, Min; An, Bingbing
Abstract: Beaded fiber composites represent promising design strategies capable of simultaneously improving strength and toughness of materials. Recent experiments have shown that plastic deformation of polymer matrix is the major energy dissipation mechanism contributing to damage tolerance of the composites reinforced with beaded fibers. Motivated by the experiments, the analyses are carried out for plastic deformation of beaded fiber composites in the course of fiber pullout. The post-yield strain softening and strain hardening of polymer matrix are accounted for, and the effect of friction between the bead and polymer matrix is incorporated in the finite element simulations. It is found that plastic deformation in beaded fiber composites is strongly dependent on the plasticity characteristics of the polymer matrix. The bead displays highly localized plastic deformation with the plastic zone located in the vicinity of fiber-bead interface. For the polymer matrix exhibiting strain softening without hardening, plastic strain in the bead is larger than that in the matrix, thereby increasing the propensity of fracture at the fiber-bead interface. The strain softening followed by hardening behavior of polymer matrix enables emergence of multiple shear bands, while strain hardening plays a role in spreading plastic deformation, giving rise to large plastic zone in the polymer matrix. We have further revealed that the high level of friction between the bead and matrix can promote coalescence of shear bands in the polymer matrix. The findings of this study shed new light on the design principles of beaded fiber composites.